Evaluation of codon optimized recombinant plasmodium knowlesi merozoite surface protein-1(19) (pkMSP-1(19)) expressed in pichia pastoris - Lau, Y.L.; Cheong, F.W.; Chin, L.C.; Mahmud, R.; Chen, Y.; Fong, M.Y. (The Malaysian Society of Parasitology and Tropical Medicine, 2014)
Malaria causes high global mortality and morbidity annually. Plasmodium knowlesi has been recognised as the fifth human Plasmodium sp. and its infection is widely distributed in Southeast Asia. Merozoite surface protein-1(19) (MSP-1(19)) appears as a potential candidate for malaria blood stage vaccine as it could induce protective immunity. In this study, codon optimized P. knowlesi MSP-1(19) (pkMSP-1(19)) was expressed and purified in yeast Pichia pastoris expression system. The purified recombinant protein was further evaluated using Western blot assay using knowlesi malaria, non-knowlesi human malaria, non-malarial parasitic infections and healthy serum samples (n = 50). The sensitivity of purified pkMSP-1(19) towards detection of knowlesi infection was as 28.6% (2/7). pkMSP-1(19) did not react with all non-malarial parasitic infections and healthy donor sera, yet reacted with some non-knowlesi human malaria sera, therefore lead to a specificity of 86.0% (37/43).